PENINGKATAN KETERAMPILAN BERPIKIR KRITIS DAN KOLABORASI MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING DI SMPN 11 PASURUAN - Hidayati, Nuril (Universitas Nahdlatul Ulama Pasuruan, 2024)
This research is classroom action research (PTK) which aims to improve students' critical thinking skills and collaboration skills using the PjBL learning model in science learning which is carried out in three cycles consisting of planning, implementation, observation and reflection. This research instrument uses analysis test questions and collaboration skills observation sheets. The results of this research show that (1) Cycle I averaged critical thinking 49.03 in the low category, 89.0 for average collaboration skills in the highly collaborative category, (2) Cycle II averaged critical thinking skills 58.73 low category, average collaboration 88.2 with very collaborative category (3) Cycle III average critical thinking skills 64.6 medium category, average collaboration skills 89.4 with very collaborative category. These results lead to the conclusion that the application of the PjBL learning model can improve the critical thinking skills and collaboration skills of class VIII C students at SMPN 11 Pasuruan.